רגע אוטוביוגרפי צלאן: צלאן, דה־מאן ודיבור - שיבולת עומר (מכאן, 2016)
Impressions of Paul Celan’s almost too perfect poem, Death Fugue, and other poems are recorded. Then various consequent issues are raised: How much control can be exercised in texts and life? Are metaphors hints of truths, or can they sometimes be too pretty? And what is the role of physical sounds, of words pronounced, and of the unconscious body, even in seemingly mind- or spirit-related issues? Paul de Man’s essay, Autobiography as Defacement, along with the author’s experience as an adolescent stutterer as well as other autobiographical details, are examined and used in an attempt to approach these and other questions.